Menumbuhkan Rasa Solidaritas Dalam Organisasi - Evi Lorita; Harius Eko Saputra; Yusuarsono Yusuarsono; Antonio Imanda; Marida Sariningsih; Bando Amin C. Kader; Mirwansyah Mirwansyah (Jurnal Dehasen Untuk Negeri, 2023)
Community Service (PKM) is carried out in the form of public dialogue with activity participants consisting of students, lecturers and education staff at the Public Administration Study Program, Dehasen University, Bengkulu. This PKM activity aims to provide insight and knowledge about the form and meaning of Social Solidarity for the Millennial Generation in the Public Administration Student Association Organization, Dehasen University, Bengkulu. This activity was carried out in one day at the Dehasen University Bengkulu Teaching Farm. The benefit of this PKM activity is that participants can understand the importance of knowing the meaning of solidarity, so that by knowing and understanding the meaning of solidarity in the organization it is hoped that this meaning can indirectly be embedded and imprinted in the souls of HIMAPLIK members and administrators themselves. It is also hoped that with this activity, HIMAPLIK members and administrators can become HIMAPLIK as a forum for forming responsible and disciplined characters, and encouraging them to be able to develop positive activities for the betterment of the organization.